FRI0455 Serum Surfactant Protein D in Systemic Sclerosis Lung Fibrosis by Presence or Absence of Gastroesophageal Reflux: A Crossectional Monocentric Study. (9th June 2015) - Sosnovskaya, A.; Fomin, V.; Novikov, P.; Frerix, M.; Mukhin, N.
Abstract : Background: Serum surfact protein D (SP-D) levels are elevated in systemic sclerosis interstitial lung disease (SSc-ILD) (1). Gastroesophageal reflux disease (GERD) is suggested to be a risk factor for SSc-ILD (2). However, previous studies did not analyze SP-D by subgroups of SSc-ILD patients with and without GERD. Objectives: Aim of our study was to evaluate SP-D as a biomarker of severity of SSc-ILD in the presence or absence of GERD. Methods: 56 SSc patients underwent chest computertomography and lung function test to evaluate ILD, and gastroesophagoscopy for confirmation/exclusion of GERD. Extend of lung fibrosis >20%, presence of ground-glass opacity (GGO) and honey combing (HC) were compared between SSc-ILD patients with and without GERD by chi-square test. Serum samples were analyzed for SP-D by Enzyme Linked Immunosorbent Assay. Correlations were evaluated by Spearman rank correlation test. Kruskal-Wallis test or Mann–Whitney U test were used to compare SP-D levels between different patient groups (values in ng/ml, mean±SD). Results: 49 patients (87.5%) were female, mean age was 46.5±14.4 years. 43 patients had limited and 13 patients diffuse cutaneous involvement. 27 patients had coexistent ILD and GERD (group 1), 16 patients had ILD but no GERD (group 2) and 13 patients had no ILD or GERD (group 3). All patients with GERD by gastroesophagoscopy had signs of ILD by computer tomography. SSc-ILD patients with vs without GERD had statistically significant more often an extend of lung fibrosis >20% (20/37 (74.1%) vs 6/16 (37.5%, p=0.018) and tendentially more often GGO (19/27 (70.4%) vs 7/16 (43.75%), p=0.084), but there was no difference in presence of HC. The levels of SP-D were not significant different between male and female (286±97 vs 227±170, p=0.169) neither between diffuse and limited cutaneous SSc patients (291±198 vs 218±150, p=0.218). In addition, SP-D did not correlate with age (r=0.221, p=0.102) or disease duration (r=-0.164, p=0.226). SP-D levels were higher in group 1 compared to group 2 and group 3 (316±156 ng/ml vs 237±134 ng/ml va 62±19 ng/ml, p<0.001), which is shown in figure 1 . SP-D levels were highly correlated with the extend of lung fibrosis (r=0.783, p<0.001), and patients with FVC <70% had higher levels compared to patients without restrictive lung function (387±175 vs 189±130, p=0.001). Moreover, the level of SP-D was higher in SSc-ILD patients with than without GGO (334±146 vs 214±133, p=0.005) and higher in patients with than without HC (367±160 vs 223±111, p=0.002). Conclusions: ILD-SSc patients with GERD have a more severe lung involvement and higher SP-D levels then ILD-SSc patients without GERD. Moreover, SP-D levels are much lower in SSc patients without ILD or GERD. Thus, our results suggest that GERD is linked with extend of lung fibrosis and may contribute to GGO, as SP-D was a valuable biomarker to monitor the severity of SSc-ILD. References: Kumánovics et al.: Comprehensive investigation of novel serum markers of pulmonary fibrosis associated with systemic sclerosis and dermato/polymyositis. Clin Exp Rheumatol. 2008. Christmann et al.: Gastroesophageal reflux incites interstitial lung disease in systemic sclerosis: clinical, radiologic, histopathologic, and treatment evidence. Semin Arthritis Rheum. 2010. Disclosure of Interest: None declared